Su vice veris di Franco Fortini. Un’ipotesi di lettura oraziana - Pandolfo, Piergiuseppe (L'ospite ingrato, 2021)
The article focuses on the relationship between Hor. carm. 1, 4 and Franco Fortini’s vice veris, which takes its title from a syntagma of the first verse of the Horatian ode. After providing a summary of Fortini’s long literary acquaintance with Horace (significantly marked by the young poet’s bonds with Giorgio Pasquali during the university years), the aim is to show how the poetic memory of Horace’s spring in the ode 1, 4 could have acted on Fortini’s composition, inspiring the description of his spring not only through a thematic influence but also, probably, through some metrical and textual details.